Examination of access, use and trust for online health information among college students - Shen, Yi (Kansas State University, 2012)
Health disparities are prevalent among ethnic minorities, including immigrants in the United States. These disparities come in the form of low health insurance, low social economic status, ethnic discrimination, language and cultural barriers. As ethnic minorities, international students also suffer from numerous health problems that are associated with their lower social, economic and immigration status when they come to the United States. Health communication is an effective tool for increasing health literacy and for reducing health disparities. Applying the uses and gratification theory and the staged model of trust, the study was conducted among 120 American students and 135 international students to examine the extent to which access to health information, the type of information accessed, how they use it, and how they determine what trustworthy information is differed between the two groups. Key findings indicate that nutrition is the most common health topic accessed online by college students regardless of place of origin. Though both groups access online health information with the same motivation of information, they use online health information in different situations. Source credibility is the most important factor for college students in determining trustworthy health websites, and government websites and other health organization websites were found to be more trustworthy. The study also provides both theoretical and practical implications, which include consideration of ethnic backgrounds in disseminating health information through online channels and understanding the needs and motivation for people’s access to health information and how they use it to be able to meet those needs. In designing health communication campaigns that target college students, the study proposes that the differences between native-born and international students need to be taken into consideration.
Keywords: Health communication; Health disparities; Health literacy; International students; Mass Communications (0708)